2010
DOI: 10.3828/idpr.2010.08
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalising transnational migrants' activities: the impact of co-development programmes

Abstract: Immigrants and their activities occupy a central position in the debate on the migration and development nexus. The focus used to be on remittances and brain drain, but as immigrants are now participating in co-development programmes, they are often regarded as a new channel for development cooperation.Although there are high expectations concerning the contribution of immigrants and their organisations to development, research on co-development initiatives and their impact is scarce. This contribution draws o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Most of this analysis focuses on relations between local governments and migrant associations within the policy field of migrant settlement. Still, a growing body of literature extends this analysis to local funding of migrant transnational development activities (Piperno & Stocchiero, ; de Haas, ; Lacroix, ; Nijenhuis & Broekhuis, ; Østergaard‐Nielsen, ; Fauser, , ).…”
Section: Towards a Framework For Understanding The Transformation Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of this analysis focuses on relations between local governments and migrant associations within the policy field of migrant settlement. Still, a growing body of literature extends this analysis to local funding of migrant transnational development activities (Piperno & Stocchiero, ; de Haas, ; Lacroix, ; Nijenhuis & Broekhuis, ; Østergaard‐Nielsen, ; Fauser, , ).…”
Section: Towards a Framework For Understanding The Transformation Of mentioning
confidence: 99%
“…Recent studies have shown that a limited number of local governments in Spain, Italy, France, and the Netherlands have funded migrant‐led projects on development in their countries of origin (Piperno & Stocchiero, ; de Haas, ; Lacroix, ; Nijenhuis & Broekhuis, ; Østergaard‐Nielsen, ; Fauser, ). These largely qualitative studies locate government ODA funding practices in wider national or international policy trends of codevelopment.…”
Section: Introductionmentioning
confidence: 99%
“…Questions about economic growth, equity and rights are hence not objective. There is no agreed upon standard measure; measures of development are always inherently political questions [46] (p. 137), [48].…”
Section: Theoretical Framework: Labor Migration Gender and Developmentmentioning
confidence: 99%
“…In many cases, they contribute financially to their families 'back home'. In some cases, migrants are also involved in setting up projects in the areas of origin with the objective to stimulate development and/or alleviate poverty (Østergaard-Nielsen, 2011;Nijenhuis & Broekhuis, 2010;Lacroix, 2008Lacroix, , 2009Weil, 2002). Several authors have argued that being engaged in international cooperation either does not impede on migrant integration in the destination country or that it can even have a positive impact on this (for instance by increasing their self-esteem) (Portes et al, 2007;Lacroix, 2009;Bermudez, 2010;Østergaard-Nielsen, 2011;Snel et al, 2006).…”
mentioning
confidence: 99%